1977
DOI: 10.1042/bj1630531
|View full text |Cite
|
Sign up to set email alerts
|

α-Chymotrypsin as the catalyst for peptide synthesis

Abstract: alpha-Chymotrypsin (EC 3.4.21.1)-catalysed syntheses of peptides were performed with various N-acylated amino acid or peptide esters as donors, and amino acid derivatives, peptides or their derivatives as acceptors. Under optimal conditions the synthesis was almost quantitative. As acceptor nucleophiles, free amino acids or the ester derivatives were inadequate, but amino acid amides or hydrazides, di- or tri-peptides, or the amides, hydrazides and esters of the peptides were useful. The nucleophile specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(28 citation statements)
references
References 17 publications
5
23
0
Order By: Relevance
“…The rate constant for ligation varies 8-fold in going from GA to GL to GF showing a mild preference for ligating peptides containing a large hydrophobic residue at P i . This is consistent with data showing a similar preference for hydrolyzing substrates containing large hydrophobic side chains at P i (Morihara et al, 1970). However, for some dipeptide combinations the difference can be much larger; for example, Arg-Phe ligates nearly 100-fold faster than Arg-Gly (showing the importance of the P2' Phe interaction for favorable rate with Arg PI').…”
Section: A) To Sy Of Cys221 Than To the Oy Of Ser221 (492 A)supporting
confidence: 90%
See 2 more Smart Citations
“…The rate constant for ligation varies 8-fold in going from GA to GL to GF showing a mild preference for ligating peptides containing a large hydrophobic residue at P i . This is consistent with data showing a similar preference for hydrolyzing substrates containing large hydrophobic side chains at P i (Morihara et al, 1970). However, for some dipeptide combinations the difference can be much larger; for example, Arg-Phe ligates nearly 100-fold faster than Arg-Gly (showing the importance of the P2' Phe interaction for favorable rate with Arg PI').…”
Section: A) To Sy Of Cys221 Than To the Oy Of Ser221 (492 A)supporting
confidence: 90%
“…A similar trend is observed for extending the peptide substrate from PI' to P,' for hydrolysis (Morihara et al, 1970;Morihara & Oka, 1977). Moreover, the specificity determinants for both reactions are similar from PI' to P; [notably a preference for a larger hydrophobic side chain at P2'; Table V and Morihara et al (1970)l. Taken together, these data suggest that the substrate-binding determinants in the S221C/P225A mutant for ligation are essentially the same as those in wild-type subtilisin for hydrolysis.…”
Section: N F I B Itorsupporting
confidence: 68%
See 1 more Smart Citation
“…Serine and sulfhydryl endopeptidases do not catalyze reaction I in Scheme 8 but they do catalyze reactions II and IIIa (136,149) and may The results are from ref. 34.…”
Section: Use Of Serine Carboxypeptidases In Peptide Synthesismentioning
confidence: 89%
“…The structures of the acyl and amine components which may participate in the reaction are determined by the specificity of the enzyme used, and studies in this laboratory have revealed that serine carboxypeptidases, e.g. carboxypeptidase Y and the malt carboxypeptidases, as expected, catalyze only aminolysis reactions with amino acids and amino acid derivatives as amine components (33,38,196,197) as opposed to endopeptidases that in addition to amino acid derivatives also accept polypeptides as nucleophiles (136,149). Consequently, when a carboxypeptidase is used a peptide chain will only be elongated by a single amino acid residue in each aminolysis reaction.…”
Section: Use Of Serine Carboxypeptidases In Peptide Synthesismentioning
confidence: 99%